Extracellular acidity in tumor tissue upregulates programmed cell death protein 1 expression on tumor cells via proton‐sensing G protein‐coupled receptors. Issue 12 (13th September 2021) - Mori, Daichi; Tsujikawa, Takahiro; Sugiyama, Yoichiro; Kotani, Shin‐ichiro; Fuse, Shinya; Ohmura, Gaku; Arai, Akihito; Kawaguchi, Tsutomu; Hirano, Shigeru; Mazda, Osam; Kishida, Tsunao
Abstract: Acidity in the tumor microenvironment has been reported to promote cancer growth and metastasis. In our study, we examined a potential relation between extracellular acidity and expression level of the immune checkpoint molecule programmed cell death protein 1 (PD‐L1) in murine squamous cell carcinoma (SCC) and melanoma cell lines. PD‐L1 expression in the tumor cells was upregulated by culturing in a low pH culture medium. Tumor‐bearing mice were allowed to ingest sodium bicarbonate, resulting in neutralization of acidity in the tumor tissue, a decrease in PD‐L1 expression in tumor cells and suppression of tumor growth in vivo. Proton‐sensing G protein‐coupled receptors, T‐cell death‐associated gene 8 (TDAG8) and ovarian cancer G‐protein‐coupled receptor 1 (OGR1), were upregulated by low pH, and essentially involved in the acidity‐induced elevation of PD‐L1 expression in the tumor cells. Human head and neck SCC RNAseq data from the Cancer Genome Atlas also suggested a statistically significant correlation between expression levels of the proton sensors and PD‐L1 mRNA expression. These findings strongly suggest that neutralization of acidity in tumor tissue may result in reduction of PD‐L1 expression, potentially leading to inhibition of an immune checkpoint and augmentation of antitumor immunity. Abstract : What's new? Large amounts of lactate generated by tumor cells during aerobic glycolysis result in high intratumoral acidity. Acidic tumor microenvironments are associated with cancer growth, metastasis, and poor prognosis. Here, using tumor‐bearing mouse models, the authors investigated relationships between acidity and expression of the immune checkpoint molecule PD‐L1, a factor upregulated by inflammation. Analyses show that extracellular acidity upregulates PD‐L1 expression of squamous cell carcinoma and melanoma cells via proton‐sensing receptors. In cell culture, PD‐L1 upregulation was reversed upon neutralization of the acidic microenvironment, suggesting that the acidic tumor microenvironment is a potential immunomodulatory therapeutic target.